The effect of almond consumption on elements of endurance exercise performance in trained athletes - Yi, M.; Fu, J.; Zhou, L.; Gao, H.; Fan, C.; Shao, J.; Xu, B.; Wang, Q.; Li, J.; Huang, G.; Lapsley, K.; Blumberg, J. B.; et al. (Journal of the International Society of Sports Nutrition, 2014)
Background: Almonds are a healthy tree nut food with high nutrient density. Their consumption has been shown to ameliorate oxidative stress, inflammation, etc. The objective of the study was to examine the effect of almonds on elements of endurance exercise performance in trained athletes.